A Review: Analysis Atomic Absorption Spectrometry (AAS) of Heavy Metal Content in Crude Palm Oil - Veranica; Rahayu, Aster; Maryudi; Lim , Lee Wah; Anggresani, Lia (Indonesian Journal of Chemical Engineering, 2024)
Indonesia, the world's largest producer of crude palm oil (CPO), turns its oil through a series of refinement processes that include degumming, bleaching, and deodorization before it is used as cooking oil. Still, heavy metals are the main focus of CPO research. Elements known as heavy metals can have harmful effects on the human body, even in small doses. Making sure the amount of metal in CPO doesn't go over the limit is crucial. To find out how much this ingredient contributes to the heavy metal contamination in crude palm oil, more research is required. The CPO refining process is carried out with the aim of reducing free fatty acids and removing dirt or metals dissolved in CPO, which can affect the quality of cooking oil. AAS can detect metals in small amounts and provide analytical differences of up to 0.006 mg/kg.